About Geopolitical Strategy of NATO in the Black Sea Pool - A. V. Ishin (Проблемы постсоветского пространства)
In the article geopolitical strategy of North Atlantic Treaty Organization in the Black Sea pool is examined. An author examines instruments and mechanisms of policy of NATO. The special attention is spared the problem of increase of military-strategic pressure from the side of evroatlantic structures. The «ukrainian», «georgian», «romanian», «turkish» factors is examined in the article.Attempts from the side of NATO to use these factors for strengthening of pressure on opponents having no prospects and do damage international relations. Interests of policy of neighbourliness suffer. Thus expressing interests of transnational soldiery, financial and industrial structures, the USA and their allies intrude in other civilization and politic space.An author comes to the conclusion, that experience of the last decade testifies with all evidence about strategic absence of any prospect of attempts of the use of the Black Sea area as a buffer area of isolation and inhibition of Russia. Exactly after the foreign-policy going of Russian diplomacy near development of the Black Sea region is the future.Changing of accents from a geopolitical rivalry and fight for the «spheres of influence» to mutually beneficial partnership and clear distributing of mutual spheres of responsibility for maintenance of international stability opens on principle new prospects and for a wide collaboration in the field of ecology, rational use of natural resources, development of rekreacionnoy infrastructure.